Factors affecting job satisfaction: a case study of private universities of Pakistan. - Hanif, Faquia; Alwi, S Khurram Khan; Malik, Mariyam; Farooqui, Mahnoor (The journal of contemporary issues in business and government, 2021)
This study aims to investigate how the interpersonal relationship and promotion opportunities associate with job satisfaction of academic staff permanently employed in private sector higher education institutions.It was a quantitative research with correlational research design. A questionnaire was developed to collect data from 150 permanent faculty members of the private sector higher education institutions in Karachi, Pakistan. Descriptive statistics, partial correlation, Anova and collinearitytests were used to analyze the data collected and model developed for the study. Results of the study revealed that interpersonal relationships at work and promotion opportunities are the factors positively related with the job satisfaction of the permanent academics employed in private sector higher education institutions. Future research can replicate the framework of this study in other settings and for comparative studies in other organizations. Time and Cost, two constraints kept study restricted to only 150 permanent academics employed in private sector higher education institutions of Karachi Pakistan. This paper will contribute to the existing literature about positive relationship among interpersonal relationship, promotion opportunities and job satisfaction of academics permanently employed in higher education institutions. This study will benefit management of the private sector higher education institutions and government authorities to revisit their current practices and policies related to the phenomenon investigated.